GAMBARAN TEKANAN DARAH DAN INDIKATOR OBESITAS WANITA USIA SUBUR DI WILAYAH KERJA PUSKESMAS TLOGOSARI WETAN KOTA SEMARANG - Haryuti Haryuti; Lintang Dian Saraswati; Ari Udiyono; M. Sakundarno Adi (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Women of childbearing age had high risk in cardiovascular disease like high blood pressure and obesity. Throughout a women’s life, health issues like pregnancy, and pregnancy prevention (birth control) could increase the risk of developing high blood pressure and obesity. The purpose of this research is to describe blood pressure and indicator of obesity in women of childbearing age at Public Health Center of Tlogosari Wetan, Semarang City. This research was a descriptive study with cross-sectional approach. The samples of this research included 82 women of chilbearing age which are taken by accidental sampling method and conducted the interview, filing questionnaires, and measurement waist circumference, height, weight and blood pressure. The average of waist circumference was 85,44 cm, sistolic blood pressure was 132,71 mmHg, diastolic blood pressure was 86,21 mmHg, BMI was 27,71 kg/m2. Majority of samples have central obesity (87,8%), hypertension grade I of sistolic blood pressure (32,9%), hypertension grade I of diastolic blood pressure (46,3%), have obese grade I (59,8%). Most of samples have high risk of cardiovascular disease especially because high blood pressure and obesity. Women of childbearing age sholud control blood pressure frequently, maintain healthy weight and avoid the risk factors to prevent cardiovascular disease.